Defining Contemplative Science: The Metacognitive Self-Regulatory Capacity of the Mind, Context of Meditation Practice and Modes of Existential Awareness - Dorjee, Dusana (Frontiers in Psychology, 2016)
The term ‘contemplative’ is now frequently used in the fast growing field of meditation research. Yet, there is no consensus regarding the definition of contemplative science. Meditation studies commonly imply that contemplative practices such as mindfulness or compassion are the subject of contemplative science. Such approach, arguably, contributes to terminological confusions in the field, is not conducive to the development of an overarching theory in contemplative science, and overshadows its unique methodological features. This paper outlines an alternative approach to defining contemplative science which aims to focus the research on the core capacities, processes and states of the mind modified by contemplative practices. It is proposed that contemplative science is an interdisciplinary study of the metacognitive self-regulatory capacity of the mind and associated modes of existential awareness modulated by motivational/intentional and contextual factors of contemplative practices. The metacognitive self-regulatory capacity is a natural propensity of the mind which enables introspective awareness of mental processes and behaviour, and is a necessary prerequisite for effective self-regulation supporting well-being. Depending on the motivational/intentional and contextual factors of meditation practice, changes in the meta-cognitive self-regulatory processes enable shifts in modes of existential awareness which determine our sense of self and reality. It is hypothesized that changes in conceptual processing are essential mediators between the metacognitive self-regulatory capacity of the mind, motivational/intentional factors, context of meditation practice and the modulations in modes of existential awareness. Meditation training fosters and fine-tunes the metacognitive self-regulatory capacity of the mind and supports development of motivational/intentional factors with the ultimate aim of facilitating increasingly advanced modes of existential awareness. Implications of the proposed framework for definitions of mindfulness and for future systematic research across contemplative traditions and practices are discussed. It is suggested that the proposed definition of contemplative science may reduce terminological challenges in the field and make it more inclusive of varied contemplative practices. Importantly, this approach may encourage development of a more comprehensive contemplative science theory recognizing the essential importance of first and second person methods to its inquiry, thus uniquely contributing to our understanding of the mind.